Nutrient intake and unhealthy dietary pattern of Iranian women: a cross sectional study - Hashemi, seyedeh zeinab; Vahidinia, Aliasghar; Hazavehei, Seyed Mohammad Mehdi; Karimi-Shahanjarini, Akram; Poorolajal, Jalal; Erfani, Hossein; Entezari, Mohammad Hassan; Eskandari, Zahra; Shahabadi, Sara Shahabadi (Progress in Nutrition, 2018)
Objective: The present study aimed to assess dietary pattern and nutrient intake of women to determine whether the nutrient intakes meet the Dietary Reference Intakes (DRIs). Methods: This cross-sectional dietary assessment survey was conducted between May and June 2014 in Hamadan city, the west of Iran. A random representative sample of 823 women aged 23-49 years participated in this study. The data collection tool was validated Iranian 168-item semi-quantitative food-frequency questionnaire (FFQ). Participants were classified based on energy intake, into low, normal and high energy groups (<1800, 1800 – 2200 and ≥2200 kcal/day, respectively). Results: Fat-soluble vitamins and potassium intake in all the three energy groups, iron intake in low and normal, and calcium intake in low energy group was significantly less than the DRIs. Intake of sodium, solid fat, added sugars, junk foods and refined grains was significantly more than upper recommended limit in the three energy groups. Educational level, job and income were strongly related to intake of food groups. Conclusion: The result of this dietary assessment will provide the basis for policy making and interventions that are appropriately tailored to each subgroups considering daily energy intake and socioeconomic status in improving their dietary behaviors.